2020
DOI: 10.1038/s43247-020-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

El Niño/Southern Oscillation response to low-latitude volcanic eruptions depends on ocean pre-conditions and eruption timing

Abstract: Proxy-based reconstructions of the past suggest that the Pacific ocean has often shown El Niño-like warming after low-latitude volcanic eruptions, while climate model simulations have suggested diverse responses. Here we present simulations from a coupled ocean-atmosphere model that illuminate the roles of ocean preconditioning, eruption magnitude and timing, and air-sea feedbacks in the El Niño/Southern Oscillation (ENSO) response to these eruptions. A deterministic component of the response, which dominates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
50
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 92 publications
(155 reference statements)
13
50
1
Order By: Relevance
“…Ensemble simulations with a highly simplified ENSO model 14 suggested a threshold effect that would make ENSO insensitive to all but the largest eruptions of the past millennium (approximately the magnitude of Krakatau and above). This has generally been confirmed by experiments with more realistic models [19][20][21][22]24 . However, a recent analysis of a long, monthly coral record from the heart of the tropical Pacific 25,26 suggests no uniform ENSO response to all eruptions over the last millennium, even for the largest eruptions 27 .…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Ensemble simulations with a highly simplified ENSO model 14 suggested a threshold effect that would make ENSO insensitive to all but the largest eruptions of the past millennium (approximately the magnitude of Krakatau and above). This has generally been confirmed by experiments with more realistic models [19][20][21][22]24 . However, a recent analysis of a long, monthly coral record from the heart of the tropical Pacific 25,26 suggests no uniform ENSO response to all eruptions over the last millennium, even for the largest eruptions 27 .…”
Section: Introductionsupporting
confidence: 57%
“…Previous studies have suggested that the hemispheric asymmetry of volcanic forcing is another factor that may differentially affect ENSO activity 15,20,21,24 . Therefore, we investigate the relationship between forcing parameters and the Niño 3.4 SST from LMR (Corals+Li13b6).…”
Section: Effects Of Forcing Asymmetrymentioning
confidence: 99%
“…However, a recent analysis of a long, monthly coral record from the heart of the tropical Pacific 25,26 suggests no uniform ENSO response to all eruptions over the last millennium, even for the largest eruptions 27 . This is in line with results from recent modeling studies using large ensembles that allow quantification of the influence of stochastic as well as deterministic elements 24 . Indeed, ENSO is thought to be affected by multiple uncertain or poorly constrained factors, including the phase of the quasi-biennial oscillation (QBO) 28 , the forcing magnitude, location, and season of the eruption 19,24 , as well as pre-conditioning of the ENSO state (neutral, Central Pacific El Niño, Eastern Pacific El Niño, or La Niña) 16 .…”
Section: Introductionsupporting
confidence: 91%
“…This is in line with results from recent modeling studies using large ensembles that allow quantification of the influence of stochastic as well as deterministic elements 24 . Indeed, ENSO is thought to be affected by multiple uncertain or poorly constrained factors, including the phase of the quasi-biennial oscillation (QBO) 28 , the forcing magnitude, location, and season of the eruption 19,24 , as well as pre-conditioning of the ENSO state (neutral, Central Pacific El Niño, Eastern Pacific El Niño, or La Niña) 16 . Yet, observational studies on this track are hindered by the limited number of well known eruption events, the temporal resolution of volcanic forcing reconstructions, and the spatial and temporal availability of proxy records.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation